Family Resilience Strategies to Face Environmental Changes During the Covid-19 Pandemic - Rinaldy N, Yose; Samputra, Palupi Lindiasari; Daryanto, Eko (Ridwan Institute, 2024)
Family resilience is an important issue in dealing with the Covid-19 pandemic in Indonesia, because of the negative impact not only on health aspects, but also on economic aspects that change family behavior. The purpose of this article is to present the available literature on the situation of family resilience at the family level that is required to face the new normal or adaptive process during the coronavirus outbreak. Qualitative research methods with synthetic analysis are used in this study. The data is sourced from 11 scientific articles collected through Google Scholar from 2020 to 2022. The results of the study show that the impact of the pandemic is unpredictable, posing a threat to family welfare. This is certainly a concern for family resilience that pays attention to: needs, complaints, comfort and alternative solutions, and the management of a family's expectations.